Organisational climate and organisational commitment: a case of ABC Kuching, Sarawak / Awang Irwan Awang Shawal and Zamri Tom - Awang Shawal, Awang Irwan; Tom, Zamri (2010)
ABC Kuching, Sarawak undergoes a continuous wave of change towards success and almost always, staff commitment is highlighted as a vital ingredient for the success of the institution. From the literatures reviewed, the organizational climate and organizational commitment are predictors of staff commitment; therefore, this study seeks ABC employees’ perceptions of their organizational climate and their organizational commitment. 100 employees agreed to participate in a survey that included the Personal Assessment of College Environment, a 46-item instrument comprised of four factors: institutional structure, supervisory relationship, teamwork, and student focus and the Organizational Commitment Questionnaire, an 18-item inventory that assessed three different types of commitment: affective (i.e., want to stay), continuance (i.e., need to stay), and normative (i.e., obligated to stay). The findings revealed that the employees perceived the organizational climate of their organization to be at a moderate level. The mean values for the components of the organizational climate ranged from the lowest of 3.47 to highest of 3.63 of the 5-point Likert scale. Affective commitment with mean of 3.18 appears to be the lowest among three components of the organizational commitment. It also result that organizational climate have significant positive relationship with organizational commitment. Gender, marital status, respondent length of services and respondent number of involvement in work committee demonstrated with no significant effect on organizational climate and organizational commitment.